The Economic Impact of Depression Treatment in India - Manuela Angelucci; Daniel Bennett (Institute of Labor Economics (IZA), 2021)
This study evaluates the impact of depression treatment on economic behavior in Karnataka, India. We cross-randomized pharmacotherapy and livelihoods assistance among 1000 depressed adults and evaluated impacts on depression severity, socioeconomic outcomes, and several potential pathways over 26 months. The pharmacotherapy treatments reduce depression severity, with benefits that persist after treatment concludes. They substantially increase child human capital investment, particularly for older children, and reduce risk intolerance and the incidence of negative shocks. These findings suggest two pathways through which depression may perpetuate poverty.
Keywords: I15; I18; 330; depression; health; poverty